Diferensiasi Organizational Citizenship Behavior (OCB): Studi Empiris Faktor Demografis pada Dosen Jurusan Tarbiyah STAIN Gajah Putih - Farid Fauzi; Andika Hariyanto Surbakti (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2019)
Demographic is one of the essential factors that may trigger the formation of organizational citizenship behaviour (OCB). This study investigates the level of differentiation of lecturers’ OCB profile at State Islamic College Gajah Putih based on demographic factors. The response is taken from 79 people as research sample. The data was analysed using technical analysis of Non Parametric Statistical Analysis through the Mann Whitney Test and Kruskal Wallis to determine the level of significance of the difference based on independent samples. The results of this study showed that there is a significant differentiation of OCB from several demographic predictors such as gender, employment status, years of service with a significance value of 0.001, 0.008 and 0.034 respectively. While the factors of the degree of education, career position status, and marriage do not have a significant differensiation with the value of 0.147, 0.395 and 0.358 respectively. It can be concluded that there are several predictors of demographic factors that have different and significant levels of OCB, namely gender, employment status and years of service, while predictors of education level, career position status and marital status do not have significant differences.